Os efeitos das alterações cambiais sobre as relações de custos de produção na cotonicultura em Mato Grosso - Costa, Henrique Cesar da (2019)
This present work having as main objective the measurement of the effects that exchange rate oscillations have on costs, through an imbalance model that uses a cost function based on the theory of the microeconomic firm and how these relationships occur through the main productive factors, and their respective possibilities of substitution, by the concept price elasticity of demand, proposed by Allen and Morishima. The analysis is based on the theory of duality contained in microeconomics, and uses as a methodological procedure of estimation, a cost function that is modeled on a logarithmic transcendental function. The variables are: Inputs (which include seeds, pesticides and fertilizers), capital, labor, land and other costs (taxes, costs and marketing). Analysis of inputs costs shows that inputs (fertilizers and pesticides) have the largest average share (about 59 %) of production costs. Capital participation (machinery, equipment and beneficiation) represent, on average, 13 % of operating expenses, capital and input participation largely justified by the investments made for the cultivation of cotton fiber, that is, the adoption of the new technology package, seeking to improve cotton quality and increase productivity. The direct price elasticities of factor demand showed negative signs according to the theory, confirming the concave condition of the cost function. Estimates of the direct price elasticities found showed a lower sensitivity in the demand for inputs related to inputs. A currency devaluation shock was applied in scenarios where there is a 50 % devaluation, the labor factor turned out to be of minor importance in cotton production, and the input factor with 0.5 currency devaluation increases on demand and on price. The results showed that the cotton crop benefited from the devaluation of the exchange rate, even though it caused an increase in the prices of imported inputs, and hypothetically the same may occur for other export crops. The main contributions are the promotion of knowledge for cotton farmers about possible exogenous impacts arising from exchange rate oscillations on production costs, as well as the increase in costs verified by data published by IMEA, and the results of the sensitivity of cotton activity verified by the estimates of these. elasticities. From the reading of this study, managers and entrepreneurs of this agricultural activity, will have a better understanding about the real impacts of changes in the foreign exchange market in face of the production costs arising from the productive factors market, thus allowing to assume assumptions for business management strategies.